Victorian Perspectives
XIII, 156 p.
Keywords: These essays focus on major figures, works or themes and movements of the Victorian era. They strive for fresh perspectives and aim to fill the gap in critical literature while reflecting the book's recurring concern with contexts and stratagems of presentation.